2020
DOI: 10.30534/ijatcse/2020/93922020
|View full text |Cite
|
Sign up to set email alerts
|

Forced Shifting to e-Learning during the COVID-19 Outbreak: Information Quality, System Quality

Abstract: The COVID-19 pandemic outbreak is not only affecting human health, but it is also affecting other aspects of human life, including the education sector. In many countries, the recommendation of health authorities forced the education sector to find an alternative of face-to-face session method. The distance learning method may be the best option for students in a forced situation. Even though e-learning is a hot topic, e-learning is still more of a supplement to education in normal conditions. This study wants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Students' intentions to continue studying through the online medium had the most negative perception (2.97, with only 34.4% of the students expressing interest, and the mean score for it was likewise the lowest compared to the other elements. Previous studies found similar results with most of the respondents stating that they do not intend to use E-learning in the future [17], [5], [1], [7]. A different study claims that "e-learning crack-up" perception has a significant impact on student's psychological distress [8].…”
Section: Student's Perception Toward E-learning: Satisfactionsupporting
confidence: 61%
“…Students' intentions to continue studying through the online medium had the most negative perception (2.97, with only 34.4% of the students expressing interest, and the mean score for it was likewise the lowest compared to the other elements. Previous studies found similar results with most of the respondents stating that they do not intend to use E-learning in the future [17], [5], [1], [7]. A different study claims that "e-learning crack-up" perception has a significant impact on student's psychological distress [8].…”
Section: Student's Perception Toward E-learning: Satisfactionsupporting
confidence: 61%
“…There is a wide variety of activities that both instructors and students can do, including observational learning behaviors and Practical learning behaviors. (Dwidienawati and Musrin 2020) carried out research to find the factors affecting e-learning performance and satisfaction regarding students who have to attend online education due to COVID-19. The results indicated that service quality is one factor that has a considerable effect on students' satisfaction.…”
Section: Status Of Online Education During Covid-19 Pandemicmentioning
confidence: 99%
“…This indicates that many studies can be considered as descriptive studies on the status quo of emergency remote teaching and learning. A small proportion of studies aimed to develop new measures and were explicitly concerned with psychometric analyses (e.g., Dwidienawati et al, 2020). 30.5% of studies employed qualitative data analyses, with a broad range of analysis approaches (e.g., content analysis, auto-narrative analysis), however 8.2% did not explicitly mention in their report, how they undertook their analysis.…”
Section: Fig 4 Data Collection Timelinementioning
confidence: 99%